2022
DOI: 10.3390/brainsci12060723
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Progresses and Prospects of IL-37 in Central Nervous System Diseases

Abstract: Interleukin-37 (IL-37) is an effective anti-inflammatory factor and acts through intracellular and extracellular pathways, inhibiting the effects of other inflammatory cytokines, such as IL-1β, IL-6, and tumor necrosis factor-α (TNF-α), thereby exerting powerful anti-inflammatory effects. In numerous recent studies, the anti-inflammatory effects of IL-37 have been described in many autoimmune diseases, colitis, and tumors. However, the current research on IL-37 in the field of the central nervous system (CNS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Interleukin (IL) 1F7, also known as IL-37, has an important anti-inflammatory and immunosuppressive effect. Systemic alterations of IL-1F7 have been described in cancer ( 58 ), central nervous system disorders ( 59 ) and other autoimmune and inflammatory diseases ( 60 ). Although IL-1F7 has an effective effect on pro-inflammatory cytokines such as TNF-α, IL-6, and IL-1β ( 61 ), our results showed that IL-1F7 did not change at any of the time points analyzed and showed no correlation with other inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL) 1F7, also known as IL-37, has an important anti-inflammatory and immunosuppressive effect. Systemic alterations of IL-1F7 have been described in cancer ( 58 ), central nervous system disorders ( 59 ) and other autoimmune and inflammatory diseases ( 60 ). Although IL-1F7 has an effective effect on pro-inflammatory cytokines such as TNF-α, IL-6, and IL-1β ( 61 ), our results showed that IL-1F7 did not change at any of the time points analyzed and showed no correlation with other inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, clinical research studies indicate the emerging role of the anti-inflammatory cytokine IL-37 in common CNS diseases. Although IL-37 has been previously associated with the pathogenesis of autoimmune diseases and cancer, the present review by Li et al focuses on the mechanism of action of IL-37 in CNS and the inhibition of inflammatory cytokines, such as IL-1β, IL-6, and tumor necrosis factor-α (TNF-α), indicating therapeutic potential [ 2 ].…”
mentioning
confidence: 99%